Newer than New - Cutting-edge biomechanics work thriving in the schools - Crevier, L. M. (BioMechanics Journal, 2008)
This article—the first in an ongoing BioMechanics series—highlights the research projects of graduate students from the University of Massachusetts Amherst. They are using resources granted by university funding and by outside sponsors to conduct clinically relevant research and to develop innovative techniques and devices that will advance the field of biomechanics. - Finite element tool analyzes custom foot orthoses for improved fit, function - Advanced imaging for plantar fasciitis detects differences in feet kinematics - Computer simulation depicts iliotibial band syndrome loading in runners - Magnetic resonance spectroscopy measures real-time muscle biochemistry in older adults